Pelaksanaan Uji kompetensi pada SMK Sentosa Baturaja - Yunita Trimarsiah; Sri Tita faulina; Dian Sri Agustina; Satria Novari; Muhajir Arafat; Fatimah Kesuma Astuti; Wisnu Murti (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
The implementation of the Competency Test held at SMK Sentosa Baturaja is one of the graduation standards for students at SMK Sentosa Baturaja. The purpose of carrying out these activities is to find out whether the student is competent or incompetent. The competency test participants are students majoring in tkj (network computer engineering) which totals 30 people. The implementation of the Competency Test was carried out offline at the SMK Sentosa Bhakti school itself, which began on February 02, 2022 until February 7, 2022. The method used in the community service activity is as an external examiner / assessor to provide an assessment of the results of UKK that has been done by students of SMK Sentosa Bhakti.The results of the implementation of the competency test were students who showed competency criteria of 70% by score of 80-95 competent information, and 30% with a score of 70-79 information quite competent.